Study on the Effectiveness Of Abhaya Sunthi Churna and Snehana Swedana in Tamaka Shwasa (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: In Ayurveda Shwasa is a disease of Pranvha srotasa which is explained by all the Acharya indetail. The disease, Tamaka Shwasa in the contemporary system of medicine resembles the clinical featuresof Bronchial Asthma such as dyspnea, cough and chest discomfort. The etiological factors like exposureto smoke, dust, seasonal variation and exposure to cold are also similar in both the condition. A roughestimation in India shows 10-15% of Bronchial Asthma in the age group of 5-11 year old children.Aim: present study is entitled to study the effect of Abhaya Sunthi Churna and Snehana, Swedana inmanagement of Tamaka Shwasa. Material & Methods: The present study was designed as the comparativeparallel group, interventional study, in which minimum of 30 patients were enrolled. The selected participantswere assigned to the two observational groups. Each interventional group participants were administeredwith Abhaya sunthi churna for 14 days in both the groups A and B. Also in Group A there were additionalSnehana and Swedana procedures for 7 days and in Group B consist of Churna with Conventional therapy.Results: In comparison significant results were seen only in Kasa in group A whereas other parametersshowed insignificant difference between the groups. The parameters such as Peenasa, Ghurghurkatwa,Kaphanishtivana, Asinolabhatesaukhyam and Shwasakrichrrata showed reduction individually. Thecomparative result of both the groups on Adventitious Sound, Significant result was noted on the 14th dayin group A who received Abhaya Shunthi Churna with Snehan Swedana after treatment in comparison withgroup B. Conclusion: we can conclude that the Symptoms of Tamaka Shwasa were reduced in both thegroups (A and B) but the effect of the Abhaya sunthi churna with Snehana, Swedana i.e Group A was moresignificant than Group B.